2019
DOI: 10.1371/journal.pone.0210098
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between myocardial oxygenation and blood pressure: Experimental validation using oxygenation-sensitive cardiovascular magnetic resonance

Abstract: BackgroundThe relationship between mean arterial pressure (MAP) and coronary blood flow is well described. There is autoregulation within a MAP range of 60 to 140 mmHg providing near constant coronary blood flow. Outside these limits flow becomes pressure-dependent. So far, response of myocardial oxygenation to changes in pressure and flow has been more difficult to assess. While established techniques mostly require invasive approaches, Oxygenation-Sensitive (OS) Cardiovascular Magnetic Resonance (CMR) is a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…coronary artery disease, heart failure, hypertrophic cardiomyopathies, it can be expected that this effect may in fact occur at much lower heart rates, when patients feel exertion. Guensch et al showed in a swine model that BOLD-SI only drops when oxygen demand outweighs the supply 36 . In patients with cardiovascular disease, this balance may be much more delicate and shifted, with fewer reserves on the supply side.…”
Section: Discussionmentioning
confidence: 99%
“…coronary artery disease, heart failure, hypertrophic cardiomyopathies, it can be expected that this effect may in fact occur at much lower heart rates, when patients feel exertion. Guensch et al showed in a swine model that BOLD-SI only drops when oxygen demand outweighs the supply 36 . In patients with cardiovascular disease, this balance may be much more delicate and shifted, with fewer reserves on the supply side.…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the Veterinary Services at the Department of Agriculture and Nature of the Canton Bern, Switzerland [#BE 103/14] ( 7 ). The study was carried out in accordance with national and local animal care regulations and adheres to the ARRIVE guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Inside of a clinical 3T magnetic resonance imaging scanner (MAGNETOM TRIO, Siemens Healthineers, Erlangen, Germany), MAP was adjusted in steps of 10–15 mmHg from a baseline level of 70 mmHg using urapidil and phenylephrine ( Figure 1B ), as published by our group previously ( 7 ). At each MAP-level, blood gas samples from the coronary sinus and the femoral artery were obtained, along with OS-CMR images.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations